RESPON KONSUMEN TERHADAP KINERJA BAURAN PEMASARAN JASA PADA HOTEL BINTANG MULIA DIJEMBER - Deasy Wulandari (RELASI : JURNAL EKONOMI, 2012)
The stars-hote/s seryices in Jember are very competitive. They offer different interestingseryices to attract the customers. The hotel management should give more attention to theperformance of seryices marketing mix in order to be the bes/ one and have the loyalcusfomers. This research is done to analyze the performance of servlces marketing suchas product, price, place, promotion, process. personnel and physical evidence of BintangMulia Hotel in Jember. The descriptive analysis rs used as the method of the research.The management hotel should observe each variable in the services marketing mixespecially for the product, price and promotion.